IMPROVING STUDENTS’ SPEAKING ABILITY BY USING ROLE PLAY TECHNIQUE AT SMP PANGERAN ANTASARI MEDAN - Nita Veronika Br. Sitanggang (English Language Teaching Prima Journal (ELT), 2024)
This study aimed to determine how the student's skills to speak and respond to the Role Play method. There were 32 students in eighth grade at SMP Pangeran Antasari Medan who were the study’s subjects. This study employed quantitative descriptive research, gathering data through tests and questionnaires. The study collected data in two phases. The first involved a speaking test by script. The second is a questionnaire with 10 questions. The researcher calculated the test results by looking for an average value, which was then used as supporting data when analyzing questionnaire data using descriptive statistics. The study's results revealed that students' ability to speak through Role Play achieved an average score of 77, with 62% of students answering